The role of structural breaks and time-varying conditions in the evolution of the reaction function of the Central Bank of Nigeria (Evolution of CB reaction function in Nigeria) - Abidemi C. Adegboye; Queeneth I. Emoedume (West African Journal of Monetary and Economic Integration, 2022)
n this study, we examine the evolution of the Central Bank of Nigeria's (CBN) reaction function since the adoption of the structural Adjustment Programme (SAP). We consider the role of structural breaks in the reaction function, the leading composition, as well as the driving factors behind changing weights assigned to target variables are identified. Using a Taylor-rule with forward looking conditions and interest rate smoothing, we show that multiple structural breaks exist in the reaction function for the 1994Q1 and 2002Q3 period. The study employs the GMM estimator and finds an efficiency trade-off in the inflation and output stabilisation mandates of the CBN. The study also finds that inclusion of more instruments in the CBN's reaction function tends to weaken its overall efficiency, although exchange rate management enhances the output stabilisation mandate of the function. We also find evidence that the 1994 structural break is fully explained by a shift in CBN's exchange rate management dynamics, while the 2002 break is linked with a shift in the Bank's focus on money growth. The study therefore emphasises the difficulty of the CBN to effectively manage inflation and output stabilisation simultaneously, which makes the adoption of a single predominant mandate the most efficient means of conducting interest rate- based monetary policy.
Keywords: E52; E58; E61; 330; Central Bank of Nigeria; inflation; monetary policy rate; output stabilisation Taylor rule